2020
DOI: 10.26434/chemrxiv.13288805.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Shape of Water in Zeolites and Its Impact on Epoxidation Catalysis

Abstract: Solvent structures that surround active sites reorganize during catalysis and influence the stability of surface intermediates. Within the pores of a zeolite, H<sub>2</sub>O molecules form hydrogen-bonded structures that differ significantly from bulk H<sub>2</sub>O. Spectroscopic measurements and molecular dynamics simulations show that H<sub>2</sub>O molecules form bulk-like three-dimensional structures within 1.3 nm cages, while H<sub>2</sub>O molecules coales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…The conditions used for rate measurements in this study avoid internal mass transfer constraints, as indicated by the linear dependence of turnover rates on alkene concentration (Section 3.1), 57 which is consistent with expectations based on prior studies of reactions of H 2 O 2 with alkenes in Ti substituted MFI, *BEA, and FAU at similar conditions. 29,33,58 A mass-transfer limited material would show a sub-linear dependence on alkene concentration because the mean concentration of alkenes throughout the pores would not depend linearly on the uid phase alkene concentration.…”
Section: Epoxidation Turnover Rate Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…The conditions used for rate measurements in this study avoid internal mass transfer constraints, as indicated by the linear dependence of turnover rates on alkene concentration (Section 3.1), 57 which is consistent with expectations based on prior studies of reactions of H 2 O 2 with alkenes in Ti substituted MFI, *BEA, and FAU at similar conditions. 29,33,58 A mass-transfer limited material would show a sub-linear dependence on alkene concentration because the mean concentration of alkenes throughout the pores would not depend linearly on the uid phase alkene concentration.…”
Section: Epoxidation Turnover Rate Measurementsmentioning
confidence: 99%
“…Interactions between solvents and reactants at solid-liquid interfaces provide energetic contributions that strongly inuence zeolite-catalyzed epoxidation reactions, [27][28][29][30][31][32][33][34] among other chemistries. For example, the identity of the organic solvent affects alkene epoxidation turnover rates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13][14] Their unique structures confine molecules into small spaces and alter the reaction pathway by modulating transition states as seen in several examples. [15][16][17] Zeolites, in general, strongly interact with water, due to the hydrophilic nature of these materials. 18 Clustered water molecules are always present adjacent to Brønsted acid sites under ambient conditions and solvate charge balancing cations and reacting molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Coordination-chemistry-driven self-assembly has emerged in the last decade as a straightforward synthetic approach and has provided increasingly intricate and functional supramolecular coordination complexes (SCCs), [1][2][3][4] including both metalorganic frameworks (MOFs) [5][6][7] and metal-organic polyhedra (MOPs). 8,9 The chemical and structural diversity, tunability, flexibility, and permanent porosity of these materials make them valuable for a wide range of applications in guest encapsulation, [10][11][12] catalysis, 13,14 sensors, [15][16][17] bioimaging agents, 18,19 and so on. Another advantage unique to SCCs is the availability of sufficient pore space to accommodate functional groups on the building blocks without interfering with their linkage or alignment.…”
Section: Introductionmentioning
confidence: 99%